2022
DOI: 10.3390/ijms23084216
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks for Mechanistic Driver Detection in Atrial Fibrillation

Abstract: The maintaining and initiating mechanisms of atrial fibrillation (AF) remain controversial. Deep learning is emerging as a powerful tool to better understand AF and improve its treatment, which remains suboptimal. This paper aims to provide a solution to automatically identify rotational activity drivers in endocardial electrograms (EGMs) with convolutional recurrent neural networks (CRNNs). The CRNN model was compared with two other state-of-the-art methods (SimpleCNN and attention-based time-incremental conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The AI platform was found to be non‐inferior in accuracy for arrhythmia detection but faster compared with the latter. Ríos‐Muñoz et al (2022) used a CNN‐based approach to detect AF starting from endocardial electrograms (EGMs).…”
Section: Resultsmentioning
confidence: 99%
“…The AI platform was found to be non‐inferior in accuracy for arrhythmia detection but faster compared with the latter. Ríos‐Muñoz et al (2022) used a CNN‐based approach to detect AF starting from endocardial electrograms (EGMs).…”
Section: Resultsmentioning
confidence: 99%
“…for re-entrant driver detection. Ríos-Muñoz et al [56] automatically identified rotors in an endocardial electrogram (EGM) using a CRNN with an accuracy of 80.04%. Liao et al [57] applied a deep learning model to an original EGM signal and detected the focal source as a potential ablation target with sensitivity, specificity, and accuracy values of 90%, 81.9%, and 82.5%, respectively.…”
Section: Deep Learning In Labeling Map Analysismentioning
confidence: 99%
“…Recently, AI has presented a major impact in the medical sciences [ 68 ] by automatizing tasks and predicting outcomes with unprecedented performance in real-time applications [ 69 , 70 , 71 ]. These advances are occurring at a fast pace in research laboratories that implement algorithms that need to learn or to be trained to achieve high accuracy performance.…”
Section: A Translational Approach In Cardiovascular Diseases: Chimera...mentioning
confidence: 99%